Black garlic for cholesterol in the community of Kudus District, Central Java - Sukesih Sukesih; Heny Siswanti; Moh Zaki Mubarok (South East Asia Nursing Research)
High cholesterol is a health problem for the body because it can cause several diseases, including heart disease, stroke, and diabetes mellitus. An increase in cholesterol in the blood can be prevented by using the active substance in garlic in the form of aliin. Allin is a chemical containing sulfur which gives garlic its distinctive aroma. The research aimed to determine the effect of black garlic on cholesterol in the community of Purwosari Kudus Village. The quasi-experimental method with pretest-posttest control group design data analysis using paired t-test and independent test of giving garlic using SOP. The research population was 40 respondents, a research sample of 34 respondents using a purposive sampling technique consisting of 17 respondents in the intervention group and 17 respondents in the control group. The results of the research show that there is an effect of black garlic on cholesterol in the community in Purwosari Kudus Village in the intervention group with a statistical test with a p-value of 0.000 < 0.05.